2021
DOI: 10.3389/frvir.2021.656788
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Induction of Micro- and Macrosomatognosia: A Virtual Hand Illusion Study

Abstract: Although body size misperceptions are known to occur under various neurological and psychiatric conditions, their neurocognitive underpinnings are not yet resolved. Accordingly, it would be beneficial to have an experimental paradigm, by which aberrant body misperceptions could be induced and systematically investigated. Expanding upon the “Virtual Hand Illusion” (VHI), this study aimed to design such a paradigm. Using a body-motion tracking system, we translated the participant's real hand position and moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Implicit embodiment measures such as the proprioceptive drift (k = 8), somatosensory evoked potentials via electroencephalography (EEG) (k = 1), skin temperature (k = 1), the self-localization drift (k = 1), or the forearm bisection task (k = 1) were, in turn, used less often. Except for two studies in which skin temperature and EEG were obtained, no other physiological embodiment measures, such as the electrodermal fear response during artificial limb threatening [26][27][28] , were collected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit embodiment measures such as the proprioceptive drift (k = 8), somatosensory evoked potentials via electroencephalography (EEG) (k = 1), skin temperature (k = 1), the self-localization drift (k = 1), or the forearm bisection task (k = 1) were, in turn, used less often. Except for two studies in which skin temperature and EEG were obtained, no other physiological embodiment measures, such as the electrodermal fear response during artificial limb threatening [26][27][28] , were collected.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, future BTI research should include different implicit measures to operationalize the illusion. One promising approach is recording the participant's electrodermal activity while the virtual hand is threatened by a virtual syringe, as implemented in some BTI studies 26,27,57 and using this physiological marker as another implicit measure of artificial hand embodiment.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In ref. [122], the authors showed that users perceive the virtual hand as part of their own body and that the sense of agency is dependent on the delay and movement variability between their real and the virtual hand. Also, in ref.…”
Section: Framework Related To Immersion and Sense Of Agency In Immers...mentioning
confidence: 99%
“…Others, such as [119], highlight the importance of developing frameworks based on appraisal to manage cognitive models, which may be useful for managing intention when addressing the SoA. Also, other research, such as [97,120,122], suggests that the sense of agency can be improved by adapting the virtual environment to the users' body movements.…”
Section: Proposed Framework To Improve the Sense Of Agency In Immersi...mentioning
confidence: 99%